Photosynthetic Bradyrhizobia Are Natural Endophytes of the African Wild Rice Oryza breviligulata - Chaintreuil, Clémence (American Society for Microbiology, 2000)
We investigated the presence of endophytic rhizobia within the roots of the wetland wild rice Oryza breviligulata, which is the ancestor of the African cultivated rice Oryza glaberrima. This primitive rice species grows in the same wetland sites as Aeschynomene sensitiva, an aquatic stem-nodulated legume associated with photosynthetic strains of Bradyrhizobium. Twenty endophytic and aquatic isolates were obtained at three different sites in West Africa (Senegal and Guinea) from nodal roots of O. breviligulata and surrounding water by using A. sensitiva as a trap legume. Most endophytic and aquatic isolates were photosynthetic and belonged to the same phylogenetic Bradyrhizobium/Blastobacter subgroup as the typical photosynthetic Bradyrhizobium strains previously isolated from Aeschynomene stem nodules. Nitrogen-fixing activity, measured by acetylene reduction, was detected in rice plants inoculated with endophytic isolates. A 20% increase in the shoot growth and grain yield of O. breviligulata grown in a greenhouse was also observed upon inoculation with one endophytic strain and one Aeschynomene photosynthetic strain. The photosynthetic Bradyrhizobium sp. strain ORS278 extensively colonized the root surface, followed by intercellular, and rarely intracellular, bacterial invasion of the rice roots, which was determined with a lacZ-tagged mutant of ORS278. The discovery that photosynthetic Bradyrhizobium strains, which are usually known to induce nitrogen-fixing nodules on stems of the legume Aeschynomene, are also natural true endophytes of the primitive rice O. breviligulata could significantly enhance cultivated rice production.